2017
DOI: 10.1038/srep45154
|View full text |Cite
|
Sign up to set email alerts
|

Potential of biosynthesized silver nanoparticles using Stenotrophomonas sp. BHU-S7 (MTCC 5978) for management of soil-borne and foliar phytopathogens

Abstract: Stenotrophomonas sp. is emerging as a popular microbe of global concern with various potential ecological roles. Biosynthesis of gold and silver nanoparticles (AgNPs) using this bacterial strain has shown promising applications in life sciences. However, there is no report on efficient agricultural applications of biosynthesized AgNPs using Stenotrophomonas sp. In this regard, successful biosynthesis of AgNPs using Stenotrophomonas sp. BHU-S7 (MTCC 5978) was monitored by Uv-visible spectrum showing surface pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(33 citation statements)
references
References 99 publications
0
32
0
1
Order By: Relevance
“…The AgNPs were biosynthesized using the culture supernatant of Stenotrophomonas sp. BHU-S7, which was isolated from agricultural farm soil [28]. The synthesis of gold NPs (AuNPs) using Bacillus subtilis isolated from Hatti Gold Mine was reported in a study.…”
Section: Microbe-based Synthesismentioning
confidence: 99%
“…The AgNPs were biosynthesized using the culture supernatant of Stenotrophomonas sp. BHU-S7, which was isolated from agricultural farm soil [28]. The synthesis of gold NPs (AuNPs) using Bacillus subtilis isolated from Hatti Gold Mine was reported in a study.…”
Section: Microbe-based Synthesismentioning
confidence: 99%
“…This difference is due to the fact that the particle size thus obtained is substantially increased by the hydrated capping agents and surface water. That is, biomolecules, such as proteins, surrounding the NPs form a highly hydrated layer, and consequently, larger hydrodynamic diameters were obtained [38, 39]. Zeta potentials provide a means of characterising NP surface charges and stabilities in aqueous suspensions, and usually NPs with zeta potential >±30 mV are considered to be stabilised [34].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly that AgNP were effective against various phytopathogens such as Alternaria alternata, Botrytis cinerea, F. oxysporum and Pythium spinosum (Kim et al, 2012). Mishra et al (2017) showed the antifungal activity of AgNPs against foliar and soil-borne phytopathogens. The inhibitory impact of different silver concentrations (2, 4, 10 μg/mL) on conidial germination was recorded under in vitro conditions.…”
Section: Introductionmentioning
confidence: 91%